Think Pair Share (TPS) Method Improves Knowledge and Attitude of School-Age Children in Vegetable Consumption - Praba Diyan Rachmawati (Journal of Global Pharma Technology, 2020)
School-age children need vegetable consumption to meet optimal growth and development needs. However, it remains a challenge to ensure the need of adequate quantities of vegetable consumption. The Think Pair Share (TPS) method may offer the solution of this problem. The aim of this study was to analyze the effect of applying health education with a think pair share on the knowledge and attitudes of school-age children in vegetable consumption. This study used a pre-experimental research design. The population in this study was  40 students at a fourth-grade elementary school and employed total sampling technique. The independent variable was health education with a think pair share learning method, while the dependent variables in this study were knowledge and attitudes. Instruments in this study were questionnaires of knowledge and attitudes. The data were analyzed using Wilcoxon Sign Rank Test statistical test  with significance α≤0.05. The results of the statistical tests showed significant effect on knowledge (p=0.000) and attitude (p=0.000) of children in consuming vegetables. Think Pair Share method can increase the knowledge and attitude of children in vegetable consumption. Future studies may consider using this method as a medium of health education to increase vegetable consumption in school-age children.Keywords: Attitude, Knowledge, Think pair share, Vegetable consumption.